INTERNET CELEBRITIES: HOW THEY AFFECT THE PURCHASE INTENTION OF GENERATION Y IN CYBERSPACE? - Ying San Lim; Tuan Hock Ng; Yi Shin Hng, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2020)
The use of social media had created a group of ordinary people who actively share their life and experiences on the social media platform. When this group of people received more and more “likes” from the audiences, they are being named as Internet celebrities. Internet celebrities who are having many followers had created the opportunity for the businesspeople to engage them in promoting and selling the products. However, despite the growth of social media and the use of social media by businesspeople, there are not many studies on internet celebrities that affecting the purchase intention among the customers in Malaysia. Hence, the problem statement of this study is to investigate the characteristic affecting internet celebrities that will affect the purchase intention of the consumers. The research had been done by collecting feedback from 200 respondents from Generation Y. An online questionnaire with 5-Likert rating scales is used to collect the data. Convenient sampling techniques were used to collect the data. The result of the study indicated that source credibility and video characteristic are the most important factors in influencing purchase intention, however, physical attractiveness and interactivity are not going to influence purchase intention. This gives an insightful thought to marketers to request internet celebrities to produce more quality videos to attract viewer attention. In terms of source credibility, marketers need to find Internet celebrities who have a more credible image to sell the company products. The justifications for the rejected hypotheses were discussed in detail in the study. The research findings of this study give marketers and academics insightful thoughts on how Internet celebrities can influence the purchase intention of Generation Y today